Genomic analysis of extra‐intestinal pathogenic Escherichia coli urosepsis. (10th April 2013) - McNally, A.; Alhashash, F.; Collins, M.; Alqasim, A.; Paszckiewicz, K.; Weston, V.; Diggle, M.
Abstract: Urosepsis is a bacteraemia infection caused by an organism previously causing an infection in the urinary tract of a patient, a diagnosis which has been classically confirmed by culture of the same species of bacteria from both blood and urine samples. Given the new insights afforded by sequencing technologies into the complicated population structures of infectious agents affecting humans, we sought to investigate urosepsis by comparing the genome sequences of blood and urine isolates of Escherichia coli from five patients with urosepsis. The results confirm the classical urosepsis hypothesis in four of the five cases, but also show the complex nature of extra‐intestinal E. coli infection in the fifth case, where three distinct strains caused two distinct infections. Additionally, we show there is little to no variation in the bacterial genome as it progressed from urine to blood, and also present a minimal set of virulence genes required for bacteraemia in E. coli based on gene association. These suggest that most E. coli have the genetic propensity to cause bacteraemia.